Nutrition strategies to maximise recovery and accelerate return to play - Phillips, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Injury in sport is often accompanied by disuse atrophy, which must be countered before a return to play. Inflammation, if present, also needs to be treated to provide an environment for a full return to play. Disuse atrophy is primarily due to a decline in muscle protein synthesis with a small contribution of increased proteolysis. In this presentation the evidence for nutritional mediation of disuse atrophy will be discussed in the context of several nutritional mediators including: protein, leucine, creatine, and n-3 polyunsaturated fatty acids. A brief word on recovery of connective tissue will also be made. All data will be taken from human studies and recommendations will be made for the practitioner for nutritional strategies to promote recovery and return to play as soon as possible after injury.